Hypnobirthing Counseling for Pregnant Women at Mahdalena Pane Clinic in 2019 - Desi Anggraini; Rizky Andriani Bakara (Science Midwifery, 2020)
The purpose of this study was to determine the effect of health education by providing counseling materials on condom contraception to couples of childbearing age in the V Village of Baru Ladang Bambu, Medan Tuntungan District. The activity carried out is to increase the knowledge of EFA that women can use contraception or not, but men can also become family planning acceptors, such as using condoms. Increase the effect of knowledge on health education by teaching men in EFA the types of contraceptives other than condoms. The types and forms of activities of this activity are providing material to EFA about contraceptives, Giving explanations to EFA, about a more detailed explanation of condoms. To achieve the objectives of the above activities, activities were carried out, among others, providing counseling materials on condom contraception to PUS, to assist women as users of family planning acceptors.